Membongkar manipulasi sejarah : kontroversi pelaku dan peristiwa - Adam, Asvi Warman (Jakarta : Penerbit Buku Kompas, 2009)
On history of Indonesia since independence until now.
Includes bibliographical references (p. 251-254) and index.
Keywords: Indonesia -- History